NUMERICAL SIMULATION WITH FINITE VOLUME METHOD FOR APPLYING VERTICAL CONFIGURATION UNDERGROUND HEAT EXCHANGER IN BANDUNG CITY - Mario Davito, Nikolas
Air conditioning systems require 40% of global energy usage. Moreover, using HCFC refrigerants can cause ozone layer depletion and global warming. This problem can be solved by using an underground heat exchanger. Ground was chosen as the main medium of heat dissipation because it has a constant temperature throughout the year. Therefore, this research was conducted to examine the application of vertical configuration underground heat exchangers in Indonesia. The model was made using the finite volume method and the heat exchanger used was the annular concentric heat exchanger for 2 types of airflow configuration. For the first configuration, the fresh air will enter through the middle while the second configuration will enter through the annulus side. The difference in temperature with the inlet and the influence of design parameters on performance will be studied. The temperature differences result and the influence of the design parameters used to make an underground heat exchanger design is made that is suitable for the conditions of the city of Bandung and compared with the commonly used air cooling system. From the simulation results for 2 types of airflow configurations, an increase in airflow velocity of 0.25 m/s will reduce system effectiveness by 31% for configuration 1 and 29.43% for configuration 2. Each increase in outer diameter of 1 inch and inside diameter of 0.25 inches will reduce system effectiveness by 56.95% for configuration 1 and 64.47% for configuration 2. Meanwhile, for each increase in ground depth of 1 m will increase system effectiveness by 22.21% for configuration 1 and 26.39% for configuration 2. The recommendation for spacing between pipe surfaces is ?102 mm. To provide the cooling needs for heat conditioning, 12 unit annular concentric heat exchanger are needed that are capable of producing a cooling capacity of 1836.12 watt.